BEYOND WELL-BEING: UPAYA SUSTAINABLE ADAPTIVE RESILIENCE MENGAKSELERASI KINERJA UMKM DI JAWA TENGAH - Supriatin, Dyah; Pratiwi, Agustin Riyan (Universitas Multimedia Nusantara, 2025)
Abstract-This study aims to analyze the effect of Employee Well-Being on the performance of MSMEs (Micro, Small, and Medium Enterprises) in Central Java by considering the mediating role of Sustainable Adaptive Resilience. The research background is based on the condition of MSMEs facing economic pressure and market uncertainty, despite efforts to improve employee well-being. A quantitative method was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) on 150 MSME respondents. The results indicate that Employee Well-Being has a significant effect on both Sustainable Adaptive Resilience and MSME performance. Furthermore, Sustainable Adaptive Resilience significantly influences MSME performance and statistically mediates the relationship between Employee Well-Being and MSME performance. These findings highlight the importance of sustainable adaptive strategies in optimizing the impact of employee well-being on business performance. This research contributes theoretically by integrating the approach of well-being and adaptive resilience in the context of MSME development and offers practical implications for policymakers and business practitioners to strengthen business resilience through investment in human resources and adaptive strategies. Keywords: Employee Well-Being; MSMEs; Sustainable Adaptive Resilience; Performance